Political Identity and Challenges for Democracy Consolidation in Indonesia - Romli, Lili (Political Science Program, Universitas Negeri Semarang, 2019)
This study explains about the emergence of political identity in Indonesia, especially in Islamic community. As a nation, Indonesia is heterogeneous in religion, ethnicity and regionalism, so the emergence of political identity cannot be avoided. Post independence, the issue of political identity, has emerged and developed. In the reformation era, the issue of political identity not only caused horizontal conflicts, but also entered political contestation in Regent, Governor and Presidential elections. In 2017 Jakarta Governor Election, the issue of political identity arose in an effort to suppress incumbents. Likewise, with the 2018 national regional head elections, political identity emerged in some regions where candidate used ethnicity and religion –based- political issues. Entering 2019 simultaneous Election, the symptoms of the emergence of political identity have also begun to appear. In several surveys, some people were worried that the emergence of political identity would color the campaign and contestation. The emergence of this phenomenon of political identity will disrupt the future of democracy in Indonesia. Moreover, the actors who use political identity are carried out by several elites and civil society, which, in fact, are the main actors for the consolidation of democracy in Indonesia.